Spinal Schwannomas; Classification, Management And Outcomes - Ayesha Sohail; Anam Tariq; Qurat-Ul-Ain Virani; Hafiza Fatima Aziz; Muhammad Shahzad Shamim (Journal of the Pakistan Medical Association, 2023)
Schwannomas are benign tumours of the peripheral nerve sheath. When they occur in spine, they are most commonly found in intradural-extramedullary location. Surgery is the mainstay of treatment. Radiation has a limited role in the management of residual or recurrent lesions not suitable for surgery. Here we discuss the existing literature on the outcomes of spinal schwannoma after surgery. Continue...